THE TREND OF TRANSITION TO THE INNOVATIVE PATH OF THE ECONOMY OF UZBEKISTAN - Numanov Kamolitdin Farkhadovich (American Journals, 2023)
The article substantiates the relevance of the role of the state in the formation of an innovative economy through close interaction between the state, scientific and educational institutions with the real sector of the economy. Based on the study of the experience of foreign countries, the mechanism and fundamental directions of state regulation of innovation activity are revealed. An analysis of the quantitative indicators of organizations and specialists performing R&D in sectors of the economy and branches of science, as well as enterprises and organizations producing innovative goods, works, services, made it possible to show the trend of innovative development of the economy of Uzbekistan.
Keywords: Uzbekistan, state policy, economy, innovation